2016
DOI: 10.1007/s00228-015-1987-8
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose pharmacokinetics and safety of azilsartan medoxomil in children and adolescents with hypertension as compared to healthy adults

Abstract: PurposeThis open-label, multicenter, single-dose study characterized the pharmacokinetics and short-term safety of azilsartan medoxomil (AZL-M) in hypertensive pediatric subjects (12–16 years [cohort 1a; n = 9]; 6–11 years [cohort 2; n = 8]; 4–5 years [cohort 3; n = 3]).MethodsModel-based simulations were performed to guide dosing, especially in 1–5-year olds, who were difficult to enroll. AZL-M was dosed according to body weight (20–60-mg tablet, cohorts 1a and 2; 0.66 mg/kg granule suspension, cohort 3). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…In the current study the mean CL/F of AZL was 1.6 L/h, which is close to the values of 1.47‐1.5 L/h reported in white and black subjects . Thus, no substantial differences in CL/F were found among racial/ethnic groups.…”
Section: Discussionsupporting
confidence: 86%
“…In the current study the mean CL/F of AZL was 1.6 L/h, which is close to the values of 1.47‐1.5 L/h reported in white and black subjects . Thus, no substantial differences in CL/F were found among racial/ethnic groups.…”
Section: Discussionsupporting
confidence: 86%
“…Body size such as BMI and total body weight is relevant for pharmacokinetics parameters including clearance and the volume of distribution . In previous reports, the clearance of perindopril and azilsartan declined in low body weight patients compared with that in high body weight patients . The incidence of hyperkalaemia associated with ACEI and ARB treatments is higher in non‐obese patients than that in obese patients .…”
Section: Resultsmentioning
confidence: 98%
“…13,14 In previous reports, the clearance of perindopril and azilsartan declined in low body weight patients compared with that in high body weight patients. 18,19 The incidence of hyperkalaemia associated with ACEI and ARB treatments is higher in non-obese patients than that in obese patients. 6 Furthermore, our results indicate the incidence of hyperkalaemia is the highest in underweight patients.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…The differences in the pharmacokinetics of AZL between the sexes and races (white and black) have also been examined. These studies revealed no clinically significant differences in AZL exposure for these populations …”
Section: Discussionmentioning
confidence: 82%
“…These studies revealed no clinically significant differences in AZL exposure for these populations. [19][20][21] In this single-center, open-label, parallel-group study in 32 subjects with mild to moderate hepatic impairment, the single-dose and multiple-dose pharmacokinetic profiles of AZL and its metabolite M-II were studied. Subjects with mild or moderate hepatic impairment did have increases in mean plasma exposure to AZL of up to 64% and to M-II of up to 40% compared with matched control subjects.…”
Section: Discussionmentioning
confidence: 99%